Minimal effects of the 2014-16 marine heatwave on fish assemblages found in eelgrass meadows on the southwestern coast of Vancouver Island, British Columbia, Canada - Robinson, Clifford L.K.; Yakimishyn, Jennifer; Evans, Rhian (Frontiers in Marine Science, 2022)
The main objective of this study was to ascertain if the 2014 to 2016 spring marine heatwaves, had a significant effect on early summer fish assemblage species composition, abundance and biomass in eelgrass meadows. It was presumed that increased water temperatures above the 90th percentile of the 30y long-term spring temperatures would result in changes to fish growth, survival and ultimately lead to changes in early summer settlement to eelgrass. We assessed this by analyzing the catch per unit effort of 18 common fish species and total fish assemblage biomass in 22 eelgrass meadows from two study areas in the northern California Current during the early summer over an 18 year period from 2004 to 2021. A control chart analysis indicated that eelgrass fish assemblages during heatwave years (2015-16) were significantly higher than the 90th percentile in Bray Curtis dissimilarity of 13 baseline years. Furthermore, analysis of similarity indicated that about one half of the 18 fish species showed variable contributing increases or decreases in catch per unit effort during the heatwave period. In addition, the same fish families from the two study areas only 100km apart did not respond in synchrony to the MHW. We could not however detect any changes in eelgrass fish species composition or assemblage level biomass during the heatwave years. An analysis of the temporal trajectory over the 17y time series in the ordination plots also revealed that changes in fish assemblage dissimilarity during the 2015 and 2016 heatwave returned quickly to levels observed during baseline. Altogether, the results of this study suggest that while the short-term (34-42 d) spring heatwave events resulted in changes fish species abundances, these changes were short-lived. Hence, our results warrant caution about generalizing about the effects of heatwaves on nearshore marine fish.